Similar Prognoses for Invasive Micropapillary Breast Carcinoma and Pure Invasive Ductal Carcinoma: A Retrospectively Matched Cohort Study in China - Liu, Yin (Public Library of Science, 2014)
PURPOSE: Invasive micropapillary breast carcinoma (IMPC) is a rare pathological finding. Few studies have compared IMPC with invasive ductal breast carcinoma (IDC) according to matched nodal status and age. To better illustrate the difference between IMPC and IDC prognoses, we conducted this cohort study. METHODS: 51 mixed or pure IMPC patients and 102 pure IDC patients were matched for nodal status and age. Clinical and biological features as well as disease-free survival (DFS) were compared between groups. RESULTS: More than one-half of IMPC consisted of mostly or exclusively IMPC component (meaning greater than 75%) and these tumors significantly correlated with a higher histologic grade (P = 0.016) and LVI positivity (P = 0.036) compared with mixed IMPC. IMPC displayed a significantly higher rate of estrogen receptor (ER) positivity and lymphovascular invasion (LVI) compared to matched IDC. Women diagnosed with IMPC had a slight, but not significant, reduced frequency for recurrence and metastasis compared to women with IDC (15.7% vs. 21.6%, P = 0.518). In the subgroup analysis, IMPC patients demonstrated significantly reduced survival (P = 0.018) compared to IDC patients in the T(1)N(2–3) subpopulation, whereas IDC patients demonstrated significantly increased recurrence and metastasis (P = 0.024) compared to IMPC patients in the T(2)N(2–3) subgroup. No difference was observed in patients with 3 or less positive lymph nodes (LNs). CONCLUSION: Although no difference in DFS was observed between IMPC and LN-matched IDC patients, IMPC patients demonstrated a significantly poorer outcome compared to IDC patients with smaller tumors and 4 or more positive LNs. The opposite results were observed in larger tumors and patients with 4 or more positive LNs. Therefore, we might advise more proactive treatment for IMPC patients with a smaller tumor size and extensive LN involvement. Furthermore, correlative IMPC studies should focus on this subset of patients to elucidate the genetic and/or biologic differences that contribute to metastatic potential.